Legal Implications of Constitutional Court Decision 168/PUU-XXI/2023 on Employment Termination within Islamic Political Jurisprudence - Tabita, Kanaya; Khalid, Khalid; Mora Matondang, Maulidya (Yayasan Lembaga Studi Makwa, 2025)
This research examines the legal implications of Constitutional Court Decision No. 168/PUU-XXI/2023 on employment termination, analysed through the framework of Islamic political jurisprudence (siyasah dusturiyyah). The primary objective is to explore how the decision aligns with constitutional protections for workers while reflecting core Islamic governance principles. Using a qualitative normative-juridical approach, the study combines statutory interpretation, doctrinal analysis, and a comparative review of classical and contemporary Islamic legal thought. Data sources include Constitutional Court documents, national labour legislation, and scholarly works on Islamic political law. The findings reveal that the decision reinforces due process in employment termination, curtails arbitrary dismissals, and upholds constitutional guarantees of justice and equality. From the perspective of siyasah dusturiyyah, these outcomes correspond to foundational principles such as justice (al-‘adl), public interest (maslahah), and the prevention of harm (dar’ al-mafasid), thereby harmonising state authority with moral and religious imperatives. The study concludes that the Court’s reasoning, although grounded in constitutional law, implicitly supports Islamic political values that emphasise balanced protection for both employers and employees while safeguarding human dignity in the workplace. The academic contribution lies in offering a conceptual model for integrating constitutional adjudication with Islamic political jurisprudence in labour law reform. This integration provides a theoretical basis for policymakers and legal practitioners to develop regulatory frameworks that are both constitutionally compliant and consistent with Islamic governance ethics, thus advancing the discourse on the convergence of national and religious legal systems in the protection of workers’ rights.